Phytotherapy and Womenʼs Reproductive Health: The Cameroonian Perspective - Njamen, Dieudonne; Mvondo, Marie Alfrede; Djiogue, Sefirin; Ketcha Wanda, Germain Jean Magloire; Magne Nde, Chantal Beatrice; Vollmer, Günter (Planta Medica, 2013)
Approximately 80 % of the population in Africa use traditional medicinal plants to improve their state of health. The reason of such a wide use of medicinal plants has been mainly attributed to their accessibility and affordability. Expectation of little if any side effects, of a “natural” and therefore safe treatment regimen, as well as traditional beliefs additionally contribute to their popularity. Several of these plants are used by women to relieve problems related to their reproductive health, during or after their reproductive life, during pregnancy, or following parturition. The African pharmacopoeia thus provides plants used for preventing and/or treating gynecological infections, dysmenorrhea, irregular menstruations, oligomenorrhea or protracted menstruation, and infertility. Such plants may then be used as antimicrobians, emmenagogues, or as suppressors of uterine flow. African medicinal plants are also used during pregnancy for prenatal care, against fetal malposition or malpresentation, retained dead fetus, and against threatened abortion. Some others are used as anti-fertilizing drugs for birth control. Such plants may exert various activities, namely, anti-implantation or early abortifacient, anti-zygotic, blastocytotoxic, and anti-ovulatory effects. Some herbs could also act as sexual drive suppressors or as a post-coital contraceptive by reducing the fertility index. A number of these plants have already been subject to scientific investigations and many of their properties have been assessed as estrogenic, oxytocic, or anti-implantation. Taking into account the diversity of the African pharmacopoeia, we are still at an early stage in the phytochemical and pharmacological characterization of these medicinal plants that affect the female reproductive system, in order to determine, through in vitro and in vivo studies, their pharmacological properties and their active principles.
Keywords: women reproductive health; African pharmacopoeia; emmenagogue; uterine flow suppressors; anti-infertility; abortifacient